2010
DOI: 10.1111/j.1475-6811.2010.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Romantic relationships and the physical and mental health of college students

Abstract: This study tested the hypothesis that, analogous to married individuals, college students in committed romantic relationships experience greater well‐being than single college students. In a sample of 1,621 college students, individuals in committed relationships experienced fewer mental health problems and were less likely to be overweight/obese. There were no significant differences between groups in frequency of physical health problems. Examination of 2 models suggested that being in a committed romantic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
211
4
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(254 citation statements)
references
References 51 publications
(50 reference statements)
9
211
4
12
Order By: Relevance
“…Kiþilerarasý iliþkilerin, özellikle de romantik iliþki-lerin bireylerin iyi oluþ halleri üzerinde önemli bir rolünün olduðu (6,7), tatmin edici yakýn iliþki baðlarýna sahip olmanýn sýkýntý ve zorluklara karþý koruyucu bir faktör olduðu belirtilmektedir (8). Romantik iliþkilerin psikolojik iyilik hali üzerindeki etkilerini inceleyen pek çok araþtýrma yapýlmýþ olsa da, romantik iliþki içerikli obsesif-kompulsif semptomlarýn oldukça yakýn bir döneme kadar araþtýr-macýlarýn dikkatini çekmediði görülmektedir (9,10).…”
Section: Gýrýþunclassified
“…Kiþilerarasý iliþkilerin, özellikle de romantik iliþki-lerin bireylerin iyi oluþ halleri üzerinde önemli bir rolünün olduðu (6,7), tatmin edici yakýn iliþki baðlarýna sahip olmanýn sýkýntý ve zorluklara karþý koruyucu bir faktör olduðu belirtilmektedir (8). Romantik iliþkilerin psikolojik iyilik hali üzerindeki etkilerini inceleyen pek çok araþtýrma yapýlmýþ olsa da, romantik iliþki içerikli obsesif-kompulsif semptomlarýn oldukça yakýn bir döneme kadar araþtýr-macýlarýn dikkatini çekmediði görülmektedir (9,10).…”
Section: Gýrýþunclassified
“…The campus gender imbalance has been identified as a negative factor in the quantity and quality of college-going Black women's romantic experiences [21][22][23]. Schoepflin [8] found that Black women attending PWIs had a limited dating landscape, due to the limited availability of Black men and to the reluctance of White men to date Black women.…”
Section: Black Students and Intercultural Datingmentioning
confidence: 99%
“…Moreover, involvement in romantic relationships has positive effects for psychological and physical health (Braithwaite, Delevi, & Fincham, 2010;Cui, Finchman, & Pasley, 2008;Markey, Markey, & Gray, 2007). Although several variables are relevant to one's ability to develop and maintain interpersonal relationships, a critical factor is confidence in one's ability to nurture them, or relationship selfefficacy (RSE; Lopez et al, 2007).…”
Section: Copyright 2012 By Psi Chi the International Honor Society Imentioning
confidence: 99%